2014
DOI: 10.1021/es503553f
|View full text |Cite
|
Sign up to set email alerts
|

Dehalococcoides mccartyi Strain JNA Dechlorinates Multiple Chlorinated Phenols Including Pentachlorophenol and Harbors at Least 19 Reductive Dehalogenase Homologous Genes

Abstract: Pentachlorophenol and other chlorinated phenols are highly toxic ubiquitous environmental pollutants. Using gas chromatographic analysis we determined that Dehalococcoides mccartyi strain JNA in pure culture dechlorinated pentachlorophenol to 3,5-dichlorophenol (DCP) via removal of the ortho and para chlorines in all of the three possible pathways. In addition, JNA dechlorinated 2,3,4,6-tetrachlorophenol via 2,4,6-trichlorophenol (TCP) and 2,4,5-TCP to 2,4-DCP and 3,4-DCP, respectively, and dechlorinated 2,3,6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…The structural similarity between chlorobenzenes and PCBs could account for this overlap in substrate specificity. D. mccartyi strain JNA is a pure culture that not only was most recently shown to reduce chlorophenols (Fricker et al 2014) but has also been shown to respire by dechlorinating Aroclor 1260 congeners, primarily by flanked meta dechlorination (Process N) (LaRoe et al 2014). Unlike strains CG1, CG4, and CG5, specific RDases in strain CBDB1 have not been implicated in dechlorination of PCB congeners.…”
Section: Discussionmentioning
confidence: 99%
“…The structural similarity between chlorobenzenes and PCBs could account for this overlap in substrate specificity. D. mccartyi strain JNA is a pure culture that not only was most recently shown to reduce chlorophenols (Fricker et al 2014) but has also been shown to respire by dechlorinating Aroclor 1260 congeners, primarily by flanked meta dechlorination (Process N) (LaRoe et al 2014). Unlike strains CG1, CG4, and CG5, specific RDases in strain CBDB1 have not been implicated in dechlorination of PCB congeners.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophenols are widely used in industry (Peng et al., ). The chlorinated compounds are released into the environment in a variety of ways, such as by discharge of phenolic wastewater, the use of pesticides, and manufacture of pharmaceuticals (Fricker, LaRoe, Shea, & Bedard, ; Marković et al., ). Many chlorophenols have “carcinogenic, teratogenic, and mutagenic” effects, and they are recognized as hazardous environmental pollutants (Khan, Mondal, & Sabir, ; Li et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Chlorophenols are widely used in industry . The chlorinated compounds are released into the environment in a variety of ways, such as by discharge of phenolic wastewater, the use of pesticides, and manufacture of pharmaceuticals (Fricker, LaRoe, Shea, & Bedard, 2014;Marković et al, 2015). Many chlorophenols have "carcinogenic, teratogenic, and mutagenic" effects, and they are recognized as hazardous environmental pollutants (Khan, Mondal, & Sabir, 2011;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%